A case study on cost-benefit analysis for process industry equipment - Muhammad Syahril Ilham, Azhar (2025)
This study investigates the integration of safety measures and cost analysis for critical process equipment in the production of 2-ethylhexanol. The research focuses on pumps, storage tanks, and separators, which are essential for material handling, storage, and separation. Piping and Instrumentation Diagrams (P&ID) validated by Dato’ Ir. Jeffrey Khor Chooi Beng, a Professor and Board Member of IChemE Malaysia, were utilised for equipment selection and analysis. A Hazard and Operability (HAZOP) analysis identified potential risks and recommended safeguards, including control valves, pressure relief valves, and temperature sensors. Additionally, a preliminary cost-benefit analysis (CBA) was conducted to evaluate the economic feasibility of implementing these safety measures. The findings provide actionable insights for optimising safety investments while ensuring operational efficiency and compliance with industrial safety standards.